A new blood glucose management algorithm for type 2 diabetes: a position statement of the Australian Diabetes Society. Issue 11 (15th December 2014) - Gunton, Jenny E; Cheung, N Wah; Davis, Timothy M E; Zoungas, Sophia; Colagiuri, Stephen
Summary: Lowering blood glucose levels in people with type 2 diabetes has clear benefits for preventing microvascular complications and potential benefits for reducing macrovascular complications and death. Treatment needs to be individualised for each person with diabetes. This should start with selecting appropriate glucose and glycated haemoglobin targets, taking into account life expectancy and the patient's wishes. For most people, early use of glucose‐lowering therapies is warranted. A range of recently available therapies has added to the options for lowering glucose levels, but this has made the clinical pathway for treating diabetes more complicated. This position statement from the Australian Diabetes Society outlines the risks, benefits and costs of the available therapies and suggests a treatment algorithm incorporating the older and newer agents.